Review of deployment controllers for space tethered system - Teik Hong, Aaron Aw; Varatharajoo, Renuganth; Chak, Yew Chung (Elsevier, 2025)
This review article investigates the performance of newly designed controllers for Tethered Space Systems (TSS) deployment, comparing them to past and current research. Specifically, the study delves into the PD type controller, known for its simplicity and early development. While PD controllers adequately manage non-coplanar scenarios with external perturbations, they are limited to linearized cases. In contrast, advanced controllers like Sliding Mode Control (SMC) effectively handle TSS's highly nonlinear dynamics due to their robust nature. The study introduces a sigma function, derived from Djebli's literature, to regulate tether deployment rate and length across all controllers. Simulation results demonstrate the feasibility of controlling out-of-plane libration angles solely through the tether tension. Among the controllers tested, the advanced sigma-SMC exhibits superior accuracy during deployment, while the modified SMC deploys the tether fastest albeit with significant steady-state errors and deflection angles. Numerical results show that the original SMC controller performs well as the most fuel-efficient option. This comparison focuses solely on tether deployment with J2 and gravity-gradient perturbations, offering a foundation for further exploration into TSS missions, including factors like aerodynamic drag, solar radiation, third body perturbations, tether flexibility, and retrieval phase control, tailored to specific mission requirements.